Raising pH of Red-Yellow Podsolik Soil by Adding Ashes and its Relation to Nitrogen Fixer Microorganism Acitivities - Murni, Pinta (Biospecies, 2009)
The aim of this study to was to observe the impact of raising the pH of red-yellow soil byadding ashes and its relation to nitrogen fixer microorganisms activities. This experiment wasconducted using completely randomized design. The treatment is ash level i.e A = 0 g (control), B =20 g, C = 30 g, D = 40g, E = 50g, and F = 60g in 5 Kg of soil. The experiment was tested onsoybean (Glycine max (L.) Merr.). Measurement included soil pH both before and after treatment andthe number and biomass of nodules. The results of the study show that ashes significantly increasesoil pH (between 1,39 and 1,74 point) and significantlt affect on the number and biomass ofnodules. The highest number of nodules was found on treatment C and D, whereas the highestbiomass was on C and E. The optimal ash concentration to increases red-yellow podsolik soil pH andformation of nodule in Soybean is 30 to 50 g in 5 Kg soil.